Selective Production of Green Hydrocarbons from the Hydrotreatment of Waste Coconut Oil over Ni- and NiMo-supported on Amine-functionalized Mesoporous Silica - Wega Trisunaryanti; Savitri Larasati; Triyono Triyono; Cahyarani Paramesti; Nugroho Raka Santoso (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In order to overcome the depletion of energy resources, the production of fuel from a renewable source (green fuel) has aroused attention. The present work serves as a comparative study for green fuel production by utilizing monometallic Ni and bimetallic NiMo loaded on amine-functionalized mesoporous silica (MS). Two types of catalysts, denoted as Ni/NH2-MS and NiMo/NH2-MS, were prepared and evaluated for its catalytic activity in the hydrotreatment of waste coconut oil (WCO) at 450 ℃ under the flow of H2 gas (20 mL.min-1). Each catalysts were characterized by using X-ray Diffraction (XRD), Atomic Absorption Spectrometer (AAS), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and Fourier Transform Infra Red (FTIR). Study of selectivity by GC-MS showed that gasoline-range hydrocarbon, especially n-undecane, was the major compound in the liquid products generated by the two amine-functionalized catalysts prepared in this study. The result showed that monometallic Ni/NH2-MS with surface area, total pore volume, nickel loading and average pore diameter 328.68 m2.g-1, 0.25 cm3.g-1, 1.90 wt%, 3.10 nm, respectively, exhibited the best performance in producing liquid hydrocarbon and generated higher level of liquid product (77.9 wt%) than bimetallic NiMo/NH2-MS (76.3 wt%). However, it is highlighted that adding 1.08 wt% of Mo in bimetallic NiMo/NH2-MS comprising 0.83 wt% of Ni improved the catalyst selectivity towards producing higher level of gasoline-range hydrocarbon (43 wt%). The bimetallic NiMo/NH2-MS prepared was found to have surface area, total pore volume, and average pore diameter of 325.13 m2.g-1, 0.14 cm3.g-1, 3.22 nm, respectively. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).